Discourse of Consumer Perception: How Important is Halal Value Chain at Cosmetic Products for Women? - Sari, Wina Diana; Safitri, Rachmayati Eka; Melina, Monika; Rahmat, Wahyudi; Putri, Afifah Nabila Syamima; Azizah, Assufia (Journal of Pragmatics and Discourse Research, 2024)
In the era of globalization, the rapid growth of economic, technological, and cultural aspects has significantly increased the living needs of the population. This research adopts a discourse analysis approach to explore the importance of Halal Beauty Products for Women in Indonesia, focusing on the halal supply chain management aspects within the cosmetics industry. Cosmetics have evolved into a primary necessity for enhancing women's beauty, contributing to the flourishing cosmetics industry in Indonesia. This qualitative research employs in-depth interviews with five respondents aged 17-22 to unravel consumer perceptions of Halal Beauty Products. Data collection utilizes semi-structured interviews, allowing for deeper exploration and potential adjustments to the interview process. Thematic analysis is applied to the gathered data, comprising positive reviews, celebrity endorsements, and the significance of kosher insignia in the adoption of halal cosmetics. The research identifies that while positive reviews and celebrity endorsements influence consumer perceptions, the halal symbol plays a crucial role due to limited consumer comprehension of the halal value chain. The halal logo emerges as a pivotal factor in instilling consumer confidence in the halal authenticity of cosmetics. In conclusion, consumer trust in halal cosmetics is influenced by the halal seal, endorsements, and positive reviews, even though awareness of the halal value chain remains limited among consumers. This discourse analysis sheds light on the dynamics of consumer perceptions, emphasizing the role of discourse elements in shaping trust in the halal cosmetics market.